New Guidelines in Designing Buildings Through the Study of the Key Abilities of AI in Architectural Design Process - El-Haridi, Nourhane M. (Transactions on Engineering and Computing Sciences, 2025)
The idea of artificial intelligence has changed as a result of technological developments and a better comprehension of the human mind. It now focuses on simulating human behavior rather than just carrying out intricate computations. As a result, there are numerous initiatives to incorporate AI technology into the architecture domain, interior designs encompassing design, administration, construction, real estate, and urban planning. The majority of AI solutions in this field are only somewhat intelligent at the moment, and crucial jobs still need a great deal of human supervision and involvement. There is Impact of Artificial Intelligence on Architectural Design and Construction wish provide more opportunities and challenges and could help in shaping a new design process through the integration of the artificial intelligent uses with the design process. This research highlights analytics for the ability of AI in Architecture by offering a new approach that could serve as new guidelines in designing building and inhabit our world